Adult orthodontic consultations in private dental practice: How much information do patients remember when they leave the surgery? - Ausra Grybaite; Mohammed Awawdeh; Parmjit Singh (Journal of Orthodontic Science)
OBJECTIVE: With good communication and information retention being key aspects of valid consent, this study aimed to assess adult patient information recall immediately after an orthodontic consultation. MATERIALS AND METHODS: Adults interested in bracket-based or clear aligners were invited to take part at a single private dental practice. A 45-minute consultation with one of three general dental practitioners (GDPs) primarily providing orthodontics took place. A participant self-completed questionnaire tested recall of 20 items from the consultation. Demographics such as gender, age, level of English, education level, previous orthodontic experience and having a close family member or friend who had orthodontic treatment were also recorded. RESULTS: Forty-two participants completed the questionnaire, and the information recall rate was 75% (mean score = 15). Three of the 42 participants recalled all 20 items. No statistically significant differences (P < 0.05) were found between information recall and any demographic variable, however, older participants (36 years and over) scored less (mean = 13.83) than participants 18-25 years (mean = 15.6). CONCLUSIONS: A quarter of information provided during an orthodontic consultation with a GDP in a private dental practice cannot be recalled immediately afterwards by patients and so it is recommended that any verbal or visual information is always supplemented with written information.